Boosting Studentsâ€™ Writing Competency Using Writing Workshop - Rifky Dora Wijayati (Ahmad Dahlan Journal of English Studies, 2016)
This study explores the implementation of writing workshop towards beginner college students of Universitas Ahmad Dahlan. Writing workshop known as the instruction focuses on the goal of fostering lifelong writers and it is designed with different developmental and curricular needs. There are four principles of writing workshop, (1) students will write about their own lives, (2) students will use a consistent writing process, (3) students will work in authentic ways, (4) students will be able to encourage themselves in writing independently. The writing workshop may help students to find their â€œvoiceâ€ in writing with less interference from the lecturer. Normally applied in elementary level, writing workshop is now adapted to be employed in higher education. It is become an important trail to facilitate the students in improving writing competency using continuous and integrated steps. This paper is an effort to share a down-to-earth idea of the implementation of writing workshop in higher education.This study exploits quantitative methods using studentsâ€™ feedback as the data collection technique.Â  A questionnaire was designed and distributed to 120 university students in English Education Departement at Universitas Ahmad Dahlan. Results revealed that students' feedback of the implementation of writing workshop in the class for improving their writing skills were generally positive. Through writing workshop, the writing process becomes more attractive for students. To the lecturers, act as a mentor author, modeling writing techniques and conferring with students as they move through the writing process perceptions give a diverse point of view in improving studentsâ€™ writing competency.Â Keywords: writing, writing workshop, college students